Technology and organisational culture in business analytics adoption - Atan@Mohd Salleh, Mislina (Penerbit UTeM Press, 2025)
This book presents the technological factors of the adoption of business analytics among SMEs in Malaysia. The factors contribute to the success of the adoption and implementation of business analytics across SMEs.